The pattern of grain yield response of normal and quality protein maize cultivars in stress and nonstress environments and nonstress environments - Badu-Apraku, Baffour; Lum, A.F. (2010)
Maize (Zea mays L.) cultivars combining high grain yield with elevated levels of lysine, tryptophan, and desirable endosperm modification, could reduce food insecurity and malnutrition in West and Central Africa (WCA). Sixteen early- and nine extra-early-maturing quality protein maize (QPM) and normal cultivars were evaluated under Striga hermonthica (Del.) Benth infestation and Striga-free environments in Nigeria from 2006 to 2008 to identify stable and high yielding cultivars. The extra-early normal maize cultivars 2000 Syn EE-W STR and 99 TZEF-Y STR, were similar in yield to the QPM versions under both research conditions. While TZEE-Y Pop STR C4 was superior in grain yield to its QPM version only under Striga-free conditions, TZEE-W Pop STR C4 significantly out yielded the QPM version, under both test conditions and was superior in Striga resistance. In the early maturity group, TZE-W DT STR C4 out yielded the QPM version by 21% under Striga infestation and by 10% when Striga-free. In contrast, the QPM cultivar 98 Syn WEC STR QPM C0 out yielded the normal endosperm version by 31% when Striga-infested. GGE-biplot analysis demonstrated that two extra-early and three early maturing cultivars had outstanding performance in both research environments. TZEE-W Pop STR QPM C0 and EV DT-W 99 STR QPM C0 were high-yielding and stable when Striga-infested while TZE-Y Pop DT STR C4, TZE-W Pop DT STR C4, and TZE-Y Pop STR QPM C0 were superior when Striga-free. The QPM cultivars with grain yield performance and Striga resistance comparable or superior to those of their normal endosperm versions have been developed in our program.